Corrosion stability of Sialon-based materials in acids and basic solutions. Issue 17 (1st December 2017) - Nickol, A.; Wolfrum, A.-K.; Kunz, W.; Michaelis, A.; Herrmann, M.
Abstract: The corrosion resistance of silicon nitride materials in hot aqueous solutions is mainly controlled by the stability of the grain boundary phase. The stability of α- and α/β-Sialon ceramics has not been well investigated up to now. Significant differences between these materials and ß-Si3 N4 materials can be expected. The corrosion resistance of different α- and α/β-Sialon materials with systematically changed compositions was investigated in 1 N H2 SO4 (0.5 M H2 SO4 ) and 1 N NaOH at 90 °C through determination of the weight change, the microstructural changes, and the strength. Reducing the amount of grain boundary phase was found to improve the stability significantly. The reduction in the grain boundary phase content of α-Sialon increased the probability of occurrence of strength-limiting Sialon polytypes (12H and 21R). These Sialon polytypes had a low corrosion stability and led to strength-limiting pores in the corroded state. Compared with Yb2 O3 -containing materials with the same composition, the yttria-containing materials exhibited a lower corrosion resistance.